Zaimek odzyskany - Małgorzata Stadnik (Autobiografia, 2015)
The article is on overview of the newest monograph by Roma Sendyka. In her book Od kultury “ja” do kultury “siebie”. O zwrotnych formach w projektach tożsamościowych the scholar discusses the concept of subjectivity, which happens to be lost in translation, but also significantly distinguishes concepts of I and self. The author of the monograph references research in many fields of humanities and the neurosciences, brings different meanings to evoked terminology, discusses translation proposals and confronts them with literary examples.